Effects of Guva Leaf Extract (Psidium Guajava) Against the Killness of Aedes Larvae Aegypti - Kartini Kartini; Sofia Sofia (Science Midwifery, 2022)
Content the phytochemicals present on guava seeds ( Psidium guajava ) can use to control the mosquito Aedes aegypti as vector disease Fever Dengue Hemorrhagic Fever (DHF). Because that need looking for alternative control vector made from ingredients natural. one plants that can be used for vector control is leaf guava seeds. Leaf guava seeds (( Psidium guajava ) aim for know potency extract leaf, and guava seeds ( Psidium guajava ) as larvicide Aedes aegypti and know effect extract leaf and guava seeds ( Psidium guajava ) against Dead Aedes aegypti design the research is experiment with five treatments and five replicates, respectively consists of 20 larvae. Concentration used namely 5%, 10%, 15%, 20%, and 0% (control ). Data analyzed with ANOVA one direction, Real Difference test Smallest and continue with analysis Probit ( CI 95% and = 0.05). The study shows that the effective dosage _ for LD50 is 15% concentration. Analysis Probit got an effective dose which is 11.484 %. Dosage of 5% extract leaf guava seeds ( Psidium guajava ) can kill larvae on average 5.4 tails (29%). 10% extract dose leaf and guava seeds ( Psidium guajava ) can kill larvae an average of 8 tails (40%). Dosage of 15% extract leaf guava seeds ( Psidium guajava ) can kill larvae on average 10.2 tails (51%). Dosage of 20% extract leaf guava seeds ( Psidium guajava ) can kill larvae on average 14.6 tails (73%) each dose could kill larvae, and the effective dosage is 11.484%.